MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU SEKOLAH DI MTs. AL-ISTIQAMAH HALONG KABUPATEN BALANGAN - Miranti Miranti (Cross-border, 2021)
This study aims to find and examine more deeply about: human resource management in improving the quality of schools. This research is a descriptive study using a qualitative approach and case study design. The data were obtained through observation, where the researcher functions as an instrument for conducting observations, in-depth interviews and documentation studies. The data were analyzed by interactive analysis through 3 activities, namely data reduction, data presentation and conclusion drawing. The validity of the data was obtained by extending the participation and triangulation of the data. From the results of this study, it can be explained that: 1) HR planning is designed and compiled based on the independence of the school by taking into account the characteristics of the school. 2) HR recruitment is carried out in a closed and open manner by utilizing human resources that are considered potential. 3) Selection is done openly. 4) Orientation, although not formal, is still given by introducing environmental conditions, culture and colleagues. 5) The training and development carried out have had a positive impact and influence, both for schools and personnel.